2004
DOI: 10.1103/physrevd.69.074511
|View full text |Cite
|
Sign up to set email alerts
|

Numerical reinvestigation of the Aoki phase withNf=2Wilson fermions at zero temperature

Abstract: We report on a numerical reinvestigation of the Aoki phase in lattice QCD with two flavors of Wilson fermions where the parity-flavor symmetry is spontaneously broken. For this purpose an explicitly symmetry-breaking source term hψiγ5τ 3 ψ was added to the fermion action. The order parameter ψ iγ5τ 3 ψ was computed with the hybrid Monte Carlo algorithm at several values of (β, κ, h) on lattices of sizes 4 4 to 12 4 and extrapolated to h = 0. The existence of a parity-flavor breaking phase can be confirmed at β… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 31 publications
8
49
2
Order By: Relevance
“…This can be seen on the right hand side of Figure 3 where the real part of the Polyakov loop and its susceptibility are shown as functions of κ. Therefore, if an Aoki phase were found somewhere between κ = 0.16 and 0.20, this would be in contrast to the experience gained in previous investigations (with Wilson gauge action) [6] in which no clear separation of the Aoki phase from the thermal transition has been observed. As expected for the phase diagram at µ = 0, the κ value at which the Polyakov loop rises significantly shifts to lower values when β is increased.…”
Section: Search For the Aoki Phasecontrasting
confidence: 53%
See 1 more Smart Citation
“…This can be seen on the right hand side of Figure 3 where the real part of the Polyakov loop and its susceptibility are shown as functions of κ. Therefore, if an Aoki phase were found somewhere between κ = 0.16 and 0.20, this would be in contrast to the experience gained in previous investigations (with Wilson gauge action) [6] in which no clear separation of the Aoki phase from the thermal transition has been observed. As expected for the phase diagram at µ = 0, the κ value at which the Polyakov loop rises significantly shifts to lower values when β is increased.…”
Section: Search For the Aoki Phasecontrasting
confidence: 53%
“…The expected Aoki phase for small values of β (cf. [6]) is in the µ = 0 plane, since µ = 0 explicitly breaks the associated parity-flavour symmetry. For larger values of β , a conical surface is believed to mark the thermal transition between the hadronic and quark gluon regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the sign of a particular combination of Wilson LECs -commonly denoted as c 2 ∝ −(2W 6 + W 8 ) -either the Aoki-scenario [11] or a first order, so called Sharpe-Singleton [10] scenario is realised. Numerical evidence for both scenarios has been observed in lattice QCD simulations and dedicated studies of the associated phase diagrams have been performed by several groups [13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[49,50] at large gauge couplings corresponding to values of the lattice spacing a ≥ 0.2 fm. In other studies [51,52,53] signals of first order phase transitions were found for Wilson fermions with and without the clover term, see also Ref.…”
Section: Phase Structurementioning
confidence: 99%